Transcriptome analysis reveals the potential biological function of FSCN1 in HeLa cervical cancer cells - Fengqin Guo; Yanliang Liu; Yanxiang Cheng; Qifan Zhang; Weili Quan; Yaxun Wei; Li Hong (PeerJ, 2022)
Fascin actin-bundling protein 1 (FSCN1), an actin-bundling protein associated with cell migration and invasion, is highly expressed in various tumor tissues. FSCN1 has also been reported to be a marker of increased invasive potential in cervical cancers. However, the functions of FSCN1 are still not fully understood in cervical cancers. Here, the gene expression profile of HeLa cells transfected with FSCN1 shRNA (shFSCN1) was compared with that of cells transfected with empty vector (shCtrl). The results showed that shFSCN1 extensively affected the transcription level of 5,043 genes in HeLa cells. In particular, Gene Ontology (GO) analysis showed that a large number of upregulated genes were annotated with terms including transcription regulation and DNA binding. The downregulated genes were enriched in some cancer pathways, including angiogenesis and cell adhesion. qPCR validation confirmed that FSCN1 knockdown significantly affected the expression of selected genes in HeLa cells either negatively or positively. Expression analysis in TCGA (The Cancer Genome Atlas) revealed that FSCN1 had negative correlations with several transcription factors and a positive correlation with an angiogenic factor (angiopoietin like 4, ANGPTL4) in cervical tumor tissue. In particular, validation by Western blotting showed that FSCN1 knockdown decreased the protein level of ANGPTL4. Our results demonstrated that FSCN1 is not only an actin-binding protein but also a transcriptional regulator and an angiogenic factor in cervical cancer. Thus, our study provides important insights for further study on the regulatory mechanism of FSCN1 in cervical cancer.